Reliving APEC 1996 : select documents & speeches - Ramos, Fidel V. (Manila, Philippines : Office of the President, 1997)
This volume is a sequel to "The Road to Subic: Selected Speeches on APEC by Filipino Leaders" (Manila: Office of the APEC Senior Officials' Meeting Chairman and the Foreign Service Institute, November 1996) - hereinafter cited as "Subic"; it includes works of both Filipinos and those from other APEC economies. The essays and speeches included in this present collection are grouped as follows: the speeches of the President are presented as Part I while Parts II-IV deal with the themes of "Building the Spirit of Community,"
Chapter 1. The President on APEC -- Chapter 2. Building the spirit of community -- Chapter 4. Economic and technical cooperation -- Chapter 5. Select APEC 1996 documents.
Keywords: ECONOMIC HISTORY